KARAKTERISTIK FISIKOKIMIA GELATIN KULIT IKAN AYAM-AYAM ( Abaliste stellaris ) DENGAN PRA-PERLAKUAN KONSENTRASI ASAM SITRAT - Abdul Aziz Jaziri; H. Muyasyaroh; M. Firdaus (BUANA SAINS, 2019)
Gelatin is a fibrous protein obtained by partial denaturation of collagen. Traditionally, gelatin derived  from mammals’ skins and bones, such as cow and pork. However, both mammals’ gelatin could risk for bovine spongiform encephalopathy (BSE) and foot mouth disease (FMD), besides, gelatin extracted from pork is prohibited in Islam rules. Therefore, fish processing waste is potential as a source of gelatin in terms of starry triggerfish (Abalistes stellaris) skin gelatin. The aims of this study is to characterize physichochemical of gelatin extracted from skin of starry triggerfish. The methods used in this research, experiment with completely randomized design (CDR) by soaking different concentrations of citric acid (0.2; 0.4; and 0.6 M). The results showed that the concentrations of citric acid  had significantly different (P0.05) on the yield, viscosity, gel strength, and fat content of starry triggerfish skin gelatin. On the other hand, the pH, melting point, galling point, protein, moisture, and ash value of starry triggerfish skin gelatin did not perform significantly different (P0.05). The most properties of starry triggerfish skin gelatin meet the commercial gelatin, and it is able to as a potential alternative of halal gelatin.